Kinematic analysis of asymmetry after strength training session in Paralympic powerlifters - dos Santos, L.; Aidar, F. J.; Nobari, H.; Badicu, G.; Greco, G.; Souza, R. L. M.; Brito, C. J.; Nikolaidis, P. T. (Sport Sciences for Health, 2024)
Background Para Powerlifting (PP) is the bench press with a single contest exercise. The rules require symmetry in lifting, but the natural tendency among humans is for asymmetry.